A cross-sectional evaluation of acceptability of an online palliative rehabilitation program for family caregivers of people with amyotrophic lateral sclerosis and cognitive and behavioral impairments - Lene Klem Olesen; Karen la Cour; Heidi With; Annette Faber Mahoney; Charlotte Handberg (BMC, 2022)
Abstract Background Amyotrophic lateral sclerosis (ALS) is a progressive fatal neurodegenerative disease. Around half of the population with ALS develop cognitive and/or behavioral impairment. Behavioral changes in persons with ALS are perceived as the strongest predictor of psychosocial distress among family caregivers. Interventions aiming to support family caregivers are emphasized as important in relation to reducing psychological distress among family caregivers. Successful healthcare interventions depend on the participants' acceptance of the intervention. Therefore, this study aims to evaluate the acceptability of a new online palliative rehabilitation blended learning program (EMBRACE) for family caregivers of people with ALS and cognitive and/or behavioral impairments. Methods A qualitative cross-sectional design using the theoretical framework of acceptability to evaluate acceptance of the intervention based on data collected through individual in-depth interviews and participant observations. Individual interviews were conducted in 10 participants post-intervention and participant observations were recorded during virtual group meetings among 12 participants. A deductive retrospective analysis was used to code both datasets in relation to the seven constructs of the theoretical framework of acceptability: affective attitude, burden, ethicality, intervention coherence, opportunity costs, perceived effectiveness, and self-efficacy. The theory of sense of coherence by Antonovsky informed the development and design of the intervention and interviews. The study adheres to the COREQ (consolidated criteria for reporting qualitative research) guidelines. Results Within the seven constructs we found that affective attitude addressed the meaning and importance of peer support and focused on the participants' needs and challenges. Burden referred to technology challenges, time pressure, and frequent interruptions during meetings. Ethicality concerned transparency about personal experiences and the exposure of the affected relative. Intervention coherence referred to a shared destiny among participants when they shared stories. Opportunity costs primary concerned work-related costs. Perceived effectiveness referred to the usefulness and relevance of peer support and the meetings that brought up new ideas on how to approach current and future challenges. Self-efficacy involved the motivation to learn more about ALS and ways to cope that were accommodated by the convenient online format. Conclusions The findings showed that the participants favored peer support and the videos that reduced feelings of loneliness and frustration but also confronted them and provided knowledge on future challenges. Further research should explore the benefits of the program and the meaning of online peer support among caregivers of people with ALS and cognitive and/or behavioral impairments. Trial registration Retrospectively registered on November 20th, 2020. ID no. NCT04638608 .